Kształtowanie się regionu wałbrzyskiego jako jednostki podziału terytorialnego - Jurek, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Specific historical names of the territorial divisions in Silesia did not use the term “region.” The region of Wałbrzych, created without taking into account historical boundaries, was separated from the Lower Silesia province until 1 January 2008. This region is a territorial unit of the third level of regionalization of the European Union. The province of Wałbrzych, which existed between 1975–1998, met the region’s criteria of the European Community and the European Union. The agglomeration of Wałbrzych exists since 2012 as an association of local government units, with respect to the number of inhabitants and the area is similar to the region of Wałbrzych and may specifically affect the development of the area. The subregion of Wałbrzych has no authority, no specific tasks and no money for the implementation of the tasks. The reflection of integration of the European regions will be empowering of all regions.
Keywords: jednostka podziału terytorialnego; decentralizacja; region wałbrzyski; aglomeracja wałbrzyska